A standard photomap of the ovarian nurse cell chromosomes for the dominant malaria vector in Europe and Middle East Anopheles sacharovi - Gleb N. Artemov; Alena I. Velichevskaya; Semen M. Bondarenko; Gayane H. Karagyan; Sargis A. Aghayan; Marine S. Arakelyan; Vladimir N. Stegniy; Igor V. Sharakhov; Maria V. Sharakhova (Malaria Journal, 2018)
Abstract Background Anopheles sacharovi is a dominant malaria vector species in South Europe and the Middle East which has a highly plastic behaviour at both adult and larval stages. Such plasticity has prevented this species from eradication by several anti-vector campaigns. The development of new genome-based strategies for vector control will benefit from genome sequencing and physical chromosome mapping of this mosquito. Although a cytogenetic photomap for chromosomes from salivary glands of An. sacharovi has been developed, no cytogenetic map suitable for physical genome mapping is available. Methods Mosquitoes for this study were collected at adult stage in animal shelters in Armenia. Polytene chromosome preparations were prepared from ovarian nurse cells. Fluorescent in situ hybridization (FISH) was performed using PCR amplified probes. Results This study constructed a high-quality standard photomap for polytene chromosomes from ovarian nurse cells of An. sacharovi. Following the previous nomenclature, chromosomes were sub-divided into 39 numbered and 119 lettered sub-divisions. Chromosomal landmarks for the chromosome recognition were described. Using FISH, 4 PCR-amplified genic probes were mapped to the chromosomes. The positions of the probes demonstrated gene order reshuffling between An. sacharovi and Anopheles atroparvus which has not been seen cytologically. In addition, this study described specific chromosomal landmarks that can be used for the cytotaxonomic diagnostics of An. sacharovi based on the banding pattern of its polytene chromosomes. Conclusions This study constructed a high-quality standard photomap for ovarian nurse cell chromosomes of An. sacharovi and validated its utility for physical genome mapping. Based on the map, cytotaxonomic features for identification of An. sacharovi have been described. The cytogenetic map constructed in this study will assist in creating a chromosome-based genome assembly for this mosquito and in developing cytotaxonomic tools for identification of other species from the Maculipennis group.